Impact of land loss on academic performance among rural adolescents in China: based on cognition-investment-performance framework - Hua, Jing; Li, Ruining (Frontiers in Environmental Science, 2023)
Introduction: As an exclusive group resulting from land requisition and demolition during the process of urbanization, the education of children belonging to land-loss farming families has received worldwide attention. However, few studies have explored the mechanisms and effects of land loss on adolescents’ academic performance. Method: Using 5,133 family samples in 2014 and 3,810 family samples in 2018 from China Family Panel Studies (CFPS), this study employed the PSM-DID and KHB models to explore the impact of land loss on the academic performance of rural adolescents. Results: The findings indicate that compared to non-land-loss families, the academic performances of adolescents in the land-loss families were lower. Additionally, land-loss families have a lower awareness of educational value. This verifies the logical mechanism of “land loss→ family education cognition→ family human capital investment→ adolescents’ academic performance.” Gender differences exist in the negative effects of land loss on adolescents’ academic performance; land loss has a greater impact on boys. Discussion: The government should strengthen the training system for land-loss farmers, improve the social security system and state of female-led families, and focus on boys affected by land loss.